Paternal age and reproductive outcomes in donor intracytoplasmic sperm injection cycles - Kannan, Haritha; Kundavi, K. M.; Rashmi, G. V.; Geetha, V.; Ranji, Geovin; Asokan, Yamini; Nivedha, K. R. Hema; Devarajan, Sandhya; Madhumitha, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Advanced paternal age has emerged as a potential contributor to adverse reproductive outcomes, though its role remains less clearly defined than that of maternal age. Donor oocyte intracytoplasmic sperm injection (ICSI) cycles provide an ideal model to study paternal effects by minimizing oocyte-related confounding effect. Objectives were to evaluate the impact of paternal age on clinical pregnancy rate (CPR) and live birth rate (LBR) in donor oocyte ICSI cycles. Methods: This retrospective observational study analysed 101 donor oocyte ICSI cycles performed at Madras Medical Mission, Chennai from 2020 to 2025. Male participants were stratified into paternal age groups: <40 years, 40-45 years, and >45 years and their outcomes in donor ICSI cycles studied. Recipient female partners ages were between 27 and 45 years. Statistical analysis was performed using chi-square tests, with p<0.05 considered significant. Results: The overall CPR was 51.4%, and the LBR was 34%. A declining trend in CPR and LBR was observed with increasing paternal age; however, these differences were not statistically significant (CPR: p=0.39; LBR: p=0.71). Miscarriage rates were higher in men aged 40 years and above (miscarriage rate p=0.340). Conclusions: Although advancing paternal age did not significantly affect CPR or LBR in donor oocyte ICSI cycles, a negative trend was observed. These findings highlight the importance of incorporating paternal age into infertility counselling and reinforce the need for larger prospective studies.